Progesterone, but not β-estradiol, enhances Porphyromonas gingivalis lipopolysaccharide-induced vascular endothelial growth factor-A expression in human THP-1 monocytes - Paiboon Jitprasertwong; Niratcha Chaisomboon; Kusuma Jamdee (Elsevier, 2013)
Background/purpose: Progesterone and estrogen levels are elevated during pregnancy and play a role in maternal immune responses. In addition, unbalanced metabolism of growth factors has been demonstrated in pregnancy tumors. Therefore, we aimed to investigate the effect of progesterone and β-estradiol on vascular endothelial growth factor-A (VEGF-A) and basic fibroblast growth factor (bFGF) messenger RNA (mRNA) expression in THP-1 monocytes in response to Porphyromonas gingivalis lipopolysaccharide (LPS). Materials and methods: THP-1 monocytes were incubated with progesterone, β-estradiol, or LPS from Escherichia coli and P. gingivalis for up to 24 hours. The expression of VEGF-A and bFGF was investigated using conventional reverse transcription polymerase chain reaction (RT-PCR) and real-time RT-PCR. Cell growth was assessed using cell proliferation assay. Results: We reported herein that progesterone, but not β-estradiol, increased VEGF-A mRNA expression in THP-1 monocytes. Significantly, progesterone enhanced VEGF-A mRNA expression in P. gingivalis LPS-treated monocytes in comparison with a treatment with P. gingivalis LPS alone. However, neither β-estradiol nor progesterone had any effect on bFGF production at mRNA levels. Conclusion: The enhancing effect of progesterone on VEGF-A mRNA expression may have a role in the pathogenesis of pyogenic granuloma in pregnant women.